Metaproteomic evidence of changes in protein expression following a change in electrode potential in a robust biocathode microbiome. Issue 20 (8th September 2015) - Leary, Dagmar H.; Hervey, William Judson; Malanoski, Anthony P.; Wang, Zheng; Eddie, Brian J.; Tender, Gabrielle S.; Vora, Gary J.; Tender, Leonard M.; Lin, Baochuan; Strycharz‐Glaven, Sarah M.; Jagtap, Pratik; Griffin, Tim; et al.
<x xml:space="preserve">Abstract</x> Microorganisms that respire electrodes may be exploited for biotechnology applications if key pathways for extracellular electron transfer can be identified and manipulated through bioengineering. To determine whether expression of proposed Biocathode‐MCL extracellular electron transfer proteins are changed by modulating electrode potential without disrupting the relative distribution of microbial constituents, metaproteomic and 16S rRNA gene expression analyses were performed after switching from an optimal to suboptimal potential based on an expected decrease in electrode respiration. Five hundred and seventy‐nine unique proteins were identified across both potentials, the majority of which were assigned to three previously defined Biocathode‐MCL metagenomic clusters: a Marinobacter sp., a member of the family Chromatiaceae, and a Labrenzia sp (abbreviated as MCL). Statistical analysis of spectral counts using the Fisher's exact test identified 16 proteins associated with the optimal potential, five of which are predicted electron transfer proteins. The majority of proteins associated with the suboptimal potential were involved in protein turnover/synthesis, motility, and membrane transport. Unipept and 16S rRNA gene expression analyses indicated that the taxonomic profile of the microbiome did not change after 52 h at the suboptimal potential. These findings show that protein expression is sensitive to the electrode potential without inducing shifts in community composition, a feature that may be exploited for engineering Biocathode‐MCL. All MS data have been deposited in the ProteomeXchange with identifier PXD001590 (http://proteomecentral.proteomexchange.org/dataset/PXD001590).